2019
DOI: 10.1073/pnas.1803794116
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent cardiac regeneration inXenopusis regulated by thyroid hormone availability

Abstract: Despite therapeutic advances, heart failure is the major cause of morbidity and mortality worldwide, but why cardiac regenerative capacity is lost in adult humans remains an enigma. Cardiac regenerative capacity widely varies across vertebrates. Zebrafish and newt hearts regenerate throughout life. In mice, this ability is lost in the first postnatal week, a period physiologically similar to thyroid hormone (TH)-regulated metamorphosis in anuran amphibians. We thus assessed heart regeneration in Xenopus laevis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 67 publications
1
48
0
1
Order By: Relevance
“…Even though a causal relationship has been suggested, the molecular mechanism is yet to be elucidated. Interestingly, thyroid hormone upregulation was observed in Xenopus to drive metamorphosis, with loss of cardiac regenerative capacity, although more than 80% of the cardiomyocytes stayed mononucleated [ 31 , 119 ]. This discrepancy between mammals and amphibians suggests that cardiomyocyte polyploidy might not be the only determining factor for cardiomyocyte regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Even though a causal relationship has been suggested, the molecular mechanism is yet to be elucidated. Interestingly, thyroid hormone upregulation was observed in Xenopus to drive metamorphosis, with loss of cardiac regenerative capacity, although more than 80% of the cardiomyocytes stayed mononucleated [ 31 , 119 ]. This discrepancy between mammals and amphibians suggests that cardiomyocyte polyploidy might not be the only determining factor for cardiomyocyte regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…frogs (Marshall et al, 2019). Although cardiomyocyte proliferation was investigated, as is often the focus in heart regeneration studies, changes relating to the ECM were also studied.…”
Section: Cardiac Regenerationmentioning
confidence: 99%
“…Although cardiomyocyte proliferation was investigated, as is often the focus in heart regeneration studies, changes relating to the ECM were also studied. Specifically, it was shown that whereas R animals (injured before metamorphosis) are able to clear deposited fibronectin and collagen and successfully complete cardiac regeneration, NR animals (injured after metamorphosis) display persistent fibrotic scars and fail to complete regeneration (Marshall et al, 2019). It therefore appears that cardiac regeneration may be stage and species dependent.…”
Section: Cardiac Regenerationmentioning
confidence: 99%
“…A new study using Xenopus laevis as a model of heart regeneration showed that the tadpole hearts can regenerate until the larvae reach metamorphosis. Excessive or reduced thyroid hormones reduce the cardiac regenerative capacity, suggesting that fine-tuning the availability of thyroid hormones may be necessary for heart regeneration ( Marshall et al, 2019 ).…”
Section: Heart Regeneration In Non-mammalian Organisms and Applicatiomentioning
confidence: 99%